A case of a sporadic malignant peripheral nerve sheath tumor of the urinary bladder with concomitant in situ urothelial carcinoma treated by transuretheral resection - Aysegul Sari; Kaan Bal; Mine Tunakan; Cemil Ozturk (Wolters Kluwer Medknow Publications, 2011)
Malignant peripheral nerve sheath tumor (MPNST) of the urinary bladder is a very rare clinical entity. The association of such a tumor with urothelial carcinoma is even more unusual. Differential diagnosis between coexisting two distinct primary tumors and carcinosarcoma of the urinary bladder is very important as both the treatment and prognosis vary widely. Herein, we report a case of an MPNST with a concomitant in situ urothelial carcinoma in a 53-year-old man. To our knowledge, this is the first documented case of MPNST of the bladder that is treated by transuretheral resection which is in contrast with the previous reports that used cystectomy.